Towards a proof of Catalan's conjecture (2012)
"Catalan's conjecture is one of those problems in number theory having an incredibly elaborate solution, despite the fact that they can be stated in a couple of lines, unambiguous as can be. Not surprisingly, it remained unsolved for more than a century and a half. The formulation of the conjecture goes back to 1844, when Crelle's Journal [5] published an excerpt from a letter the Belgian mathematician Eugène Charles Catalan sent to August Leopold Crelle, editor of Crelle's Journal..."